Decorin–induced, preeclampsia-associated microRNA-512-3p restrains extravillous trophoblast functions by targeting USF2/PPP3R1 axis - Halari, Chidambra D.; Nandi, Pinki; Sidhu, Jasmin; Sbirnac, Maria; Zheng, Michael; Lala, Peeyush K. (Frontiers in Cell and Developmental Biology, 2022)
Decorin (DCN) is a leucine-rich proteoglycan produced by chorionic villus mesenchymal cells and decidual cells during human pregnancy. Studies from our laboratory demonstrated that decidua- derived DCN restrains multiple trophoblast functions including proliferation, migration, invasion and endovascular differentiation, mediated by DCN-binding to multiple tyrosine kinase receptors expressed by the trophoblast. Furthermore, DCN was shown to be selectively over-produced by the decidua in preeclampsia (PE) subjects and elevated in the second trimester maternal plasma in PE, before the appearance of clinical signs, presenting as a predictive biomarker for PE. Micro(mi)RNAs are single-stranded non-coding RNAs (17-25 nucleotides) that typically down- regulate target genes by repressing translation or facilitating degradation of mRNAs. The human placenta expresses many miRNAs, some of which are exclusively expressed by the trophoblast. Many of these miRNAs are dysregulated in PE-associated placentas and some appear in the maternal blood as PE biomarkers. However, little is known about their contribution to the pathogenesis of PE, a multi-factorial disease associated with a hypo-invasive placenta. The objective of the present study was to examine whether exposure of extra-villous trophoblast (EVT) to DCN affects expression of specific miRNAs, and to test the role of these miRNAs in altering EVT functions. We identified miR-512-3p, as one of the DCN-induced miRNAs, also upregulated in PE placentas. It was shown to be elevated in ectopic DCN-over-expressing or exogenous DCN-treated first trimester human trophoblast cell line HTR-8/SVneo. Use of miRNA-mimics and inhibitors revealed that miR-512-3p compromised trophoblast migration, invasion and VEGF-dependent endovascular differentiation. Finally, Protein Phosphatase 3 Regulatory Subunit B, Alpha (PPP3R1), a known target of miR-512-3p, was paradoxically elevated in miR-512-3p-overexpressing trophoblast and PE-associated placentas. Using Enrichr, a tool that consists of both a validated user-submitted gene list and a search engine for transcription factors, we found that PPP3R1 elevation resulted from the miRNA binding to and targeting Upstream Transcription Factor 2 (USF2) which targeted PPP3R1. These findings reveal a novel aspect of pathogenesis of PE and biomarker potentials of this miRNA in PE.